Effect of fiber twist angle and non-uniform symmetric alignment on signal combiner - Yin, Yuyi; Ge, Tingwu; Li, Guanzheng; Xue, Chuang; Wang, Zhiyong (Frontiers in Physics, 2024)
Signal beam combiners play a pivotal role in enhancing the output power of fiber lasers, which have wide-ranging applications from industrial processing to medical and military uses. This paper explores the influence of fiber twist angle and non-uniform symmetric arrangement on the performance of 19 × 1 fiber signal combiners. A simulation model was developed to analyze the impact of these parameters under adiabatic tapering conditions and the principle of brightness conservation. The model allowed for a systematic investigation of how varying twist angles and non-uniform spacings affect the combiner's performance metrics, such as transmission efficiency and beam quality. The study found that an optimal balance between high transmission efficiency (up to 98.5%) and good beam quality (minimum M2 factor of 1.06) can be achieved when the twist angle is kept below 60° and the non-uniform spacing is maintained within 10–30 μm. These conditions ensure minimal degradation of the beam quality while maximizing the transmission efficiency of the combiner. These findings offer valuable insights into the optimization of signal combiner design, which is critical for advancing high-power fiber laser systems. By carefully controlling the fiber twist angle and non-uniform spacing, designers can achieve superior performance in fiber laser applications, thereby enhancing the overall efficiency and reliability of these systems. This research contributes to the broader field of optical engineering by providing a deeper understanding of the underlying principles that govern the performance of signal combiners.